Efficacy study of potential anti-tubercular molecules: in-vitro and ex-vivo - Nawale, Laxman; Sarkar, Dhiman (National Science Day, 2015)
Tuberculosis: Infectious disease caused by the bacillus Mycobacterium tuberculosis Second leading infectious killer after HIV/AIDS In 2013, 8.6 million TB cases were reported out of which 1.3 million died Emergence of Multi-drug resistant TB (MDR-TB) and extremely drug resistant TB (XDR) for which no drugs are available. Latency being a cause of recurring TB infection is a major problem in eradication of TB

[Et3NH][HSO4] catalyzed efficient synthesis of 5-arylidene-rhodanine conjugates and their antitubercular activity - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Research on Chemical Intermediates, 2016)
We have described a highly efficient, safer protocol for the synthesis of 5-arylidene-rhodanine conjugates catalyzed by Bronsted acidic ionic liquid [Et3NH][HSO4] in excellent yields. The protocol offers cost-effective, environmentally benign, solvent-free conditions and recycle-reuse of the catalyst. The synthesized 5-arylidene-rhodanine conjugates were characterized on the basis of (1) H NMR, C-13 NMR and HRMS spectral data. A series of 5-arylidene-rhodanine derivatives 3a-h, 4a-h were synthesized and evaluated for their in vitro antitubercular activity against dormant Mycobacterium tuberculosis H37Ra and M. bovis BCG strains. Moreover, compounds 3a, 3b, 3e, 3f, 3g, 3h and 4f exhibited good antitubercular activity and were also evaluated for anti-proliferative activity against MCF-7, A549 and HCT116 cell lines using modified MTT assay and found to be noncytotoxic. Compounds 3a-h and 4f were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards M. tuberculosis. Furthermore, in silico ADME prediction of all the tested compounds followed the criteria for orally active drug and, therefore, these compounds may have a good potential for eventual development as oral agents.

Evidence of nitrite acting as a stable and robust inducer of non-cultivability in Mycobacterium tuberculosis with physiological relevance - Gample, Suwarna P.; Agrawal, Sonia; Sarkar, Dhiman (Scientific Reports, 2019)
Tuberculosis (TB) is the ninth leading cause of death worldwide, ranking above human immunodeficiency virus. Latency is the major obstacle in the eradication of this disease. How the physiology of the pathogen changes in transition to the latent stage needs to be understood. The latent bacteria extracted from animal hosts exist in a nonculturable (NC) phase, whereas bacteria extracted from most in vitro models are culture-positive. In the present study, we observed that nitrite, up to a concentration of 5 mM, shows the growth of Mycobacterium tuberculosis (MTB) in liquid media, but this effect starts reversing at higher concentrations. At a concentration of 10 mM, nitrite induces rapid nonculturability of MTB at the aerobic stage. This noncultivable dormancy was confirmed by analyzing the characteristics of NC bacteria. Further differential gene expression analyses clearly supported the formation of a dormancy phenotype. This study will be helpful for the use of this bacillus as a dormancy model in future studies on TB latency.

Exploring the pharmacological potentials of biosurfactant derived from planococcus maritimus SAMP MCC 3013 - Waghmode, Samadhan; Swami, Sagar; Sarkar, Dhiman; Suryavanshi, Mangesh; Roachlani, Sneha; Choudhari, Prafulla; Satpute, Surekha (Current Microbiology, 2020)
Therapeutic potential of biosurfactant (BS) has been improved in recent years. Our present study deals with production of BS from Planococcus maritimus SAMP MCC 3013 in a mineral salt medium (MSM) supplemented with glucose (1.5% w/v). Further, BS has been purified and partially characterized as glycolipid type through our previous publication. Current research article aimed to evaluate biological potential of BS against Mycobacterium tuberculosis, Plasmodium falciparum and cancerous cell lines. Planococcus derived glycolipid BS was found to be a promising inhibitor of M. tuberculosis (MTB) H37Ra at IC50 64.11 +/- 1.64 mu g/mL and MIC at 160.8 +/- 1.64 mu g/mL. BS also showed growth inhibition of P. falciparum at EC50 34.56 +/- 0.26 mu M. Additionally, BS also displayed the cytotoxicity against HeLa (IC50 41.41 +/- 4.21 mu g/mL), MCF-7 (IC50 42.79 +/- 6.07 mu g/mL) and HCT (IC50 31.233 +/- 5.08 mu g/mL) cell lines. Molecular docking analysis was carried for the most popular glycolipid type BS namely Rhamnolipid (RHL) aiming to interpret the possible binding interaction for anti-tubercular and anti-cancer activity. This analysis revealed the involvement of RHL binding with enoyl reductase (InhA) of M. tuberculosis. Docking studies of RHL with tubulin directed several hydrophobic and Vander Waal interactions to exhibit anti-cancer potential. The present study will be helpful for further development of marine bioactive molecules for therapeutic applications. Their anti-tubercular, anti-plasmodial and cytotoxic activities make BS molecules as a noteworthy candidate to combat several diseases. To the best of our knowledge, this is the first report on projecting the pharmacological potential of Planococcus derived BS. Graphic